Investigation of the electrocatalytic activity of bismuth-substituted pyrochlore Y2Sn2O7 for the voltammetry determination of the antipsychotic drug. (December 2022) - Karthik, Raj; Balamurugan, Karuppaiah; Chen, Shen-Ming; Sukanya, Ramaraj; R. Chavan, Prajakta; Nguyen, Van Quang; Shim, Jae-Jin; Breslin, Carmel B.
Abstract: Pyrochlore oxides are considered active candidates for various electrochemical applications due to their cationic charges and anionic deficiency. At the same time, the cationic substitution of pyrochlore is a crucial parameter to improve the catalytic activity of electrode materials. Against this background, this article aims to synthesize bismuth-substituted defective pyrochlore-yttrium tin oxide nanoparticles (Bi0.6 Y1.4 Sn2 O7 ; BYSO NPs) and construct an electrochemical sensor for the antipsychotic chlorpromazine (CHPMZ). The catalyst was prepared by co-precipitation technique followed by thermal treatment. The analytical methods, such as p-XRD, FT-IR, TGA, and XPS, confirmed the successful substitution of Y 3+ by Bi 3+ . The morphology of the as-prepared catalysts was analyzed by the FE-SEM and TEM techniques, which shows that the size of nanoparticles is ⁓20–30 nm. From the CV results, the cationic substitution enhances the electrocatalytic oxidation of CHPMZ due to the intrinsic activity enhancement by the substitution with a large size cation and the anionic deficiency of the pyrochlore structure. Moreover, the heterogeneous rate constant of CHPMZ on BYSO/SPCE was calculated to be 4.49 × 10 −3  cm/s, indicating that the oxidation of CHPMZ on BYSO/SPCE is quasi-reversible. The electrode modified with BYSO NPs showed wider linear ranges (0.01–58.41 μM, 78.41–1158 μM), high sensitivity (1.03 μA/μM/cm 2 ) with a low detection limit of 3 nM. The modified electrodes showed good selectivity, repeatability, and excellent stability for the detection of CHPMZ. Moreover, the constructed sensor showed promising results in practical analysis with good recovery in human blood serum and urine samples. Graphical abstract: Image 1 Highlights: The defective pyrochlore Bi-substituted Y2 Sn2 O7 nanoparticles (BYSO NPs) were prepared by a simple method. A new electrochemical sensor was reported based on BYSO/SPCE for CHPMZ detection. The BYSO/SPCE exhibits good electrocatalytic activity towards CHPMZ detection. The constructed electrode owns a LOD (3 nM) and sensitivity (1.03 μA/μM/cm 2 ). The good recovery results were obtained for CHPMZ detection in real sample analysis.